ANALYSIS OF SYNTACTIC TERMS - Karimjonova Administrator (Journals Park Publishing, 2023)
Syntactic terms and grammar have its own characteristics like other concepts. Syntactic terms and their analysis will be further explored in mother tongue lessons.
Keywords: phrase, grammar, sentence, word, lexeme, phoneme.